2012
DOI: 10.1016/j.bbagrm.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The dual lives of bidirectional promoters

Abstract: The sequencing of the human genome led to many insights into gene organization and structure. One interesting observation was the high frequency of bidirectional promoters characterized by two protein encoding genes whose promoters are arranged in a divergent or “head-to-head” configuration with less than 2000 base pairs of intervening sequence. Computational estimates published by various groups indicate that nearly 10% of the coding gene promoters are arranged in such a manner and the extent of this bias is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…It has been reported that many cancer or DNA repair associated genes have bidirectional partner genes, and that tandem repeated ETS binding sites are frequently found in the 5'-upstream regions of both genes [98][99][100][101]. Therefore, expression of many DNA repair factor encoding genes is thought to be regulated by TFs that bind to GGAA motifs.…”
Section: Biological Relevance Of Bidirectional Transcriptionmentioning
confidence: 99%
“…It has been reported that many cancer or DNA repair associated genes have bidirectional partner genes, and that tandem repeated ETS binding sites are frequently found in the 5'-upstream regions of both genes [98][99][100][101]. Therefore, expression of many DNA repair factor encoding genes is thought to be regulated by TFs that bind to GGAA motifs.…”
Section: Biological Relevance Of Bidirectional Transcriptionmentioning
confidence: 99%
“…HOTAIR, on the other hand, acts in trans to repress the expression of genes in the HoxD gene cluster (53). It has been proposed that antisense lncRNAs transcribed from bidirectional promoters may be involved in the regulation of the associated sense transcripts (47,54). Such an arrangement may allow tighter transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in chickens it corresponds to an alternatively spliced, polyadenylated, antisense lncRNA, leading us to propose that the TERT promoter is bidirectional. Bidirectional promoters have been found to be pervasive in mammalian genomes, with more than 10% of known proteincoding genes being transcribed from such promoters (45)(46)(47). In humans, many lncRNAs are transcribed from bidirectional promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that co-transcription could entail co-functionality of paired gene products is supported by the observation that divergent PCG/PCG pairs in the human genome (around 10% of all PCGs) are enriched in specific functional categories, such as DNA repair and the regulation of cell cycle and metabolism. 51 As the annotated promoter region separating the TSSs of ncRNA-RB1 and RB1 is only 114 bp in size, we reasoned that the transcripts are likely to be co-expressed from a shared bidirectional promoter. Conceptually, the transcript pairs originating from relatively short bidirectional promoters should be regulated in a coordinated manner, as on nucleosome-free promoters the establishment of an active transcription environment on one TSS facilitates transcription initiation by polymerase II also at the divergent TSS.…”
Section: Discussionmentioning
confidence: 99%